Análise da estrutura populacional de Tetragonisca (Hymenoptera, Meliponini) por marcadores microssatélites e rede de interações - kulza, Rodrigo Amaral (2015)
The jataí (Tetragonisca angustula) is the most stingless bee managed by beekeepers, whose honey has many medicinal properties and it's widely distributed throughout Latin America. This bee has a variation in the coloring in a part of thorax called mesepisterno which can be black, yellow or mixed, and depending on the researcher is classified into two species (T. angustula and T. fiebrigi) or two subspecies (T. angustula angustula and T. angustula fiebrigi). Several studies have been conducted in order to elucidate this taxonomic question using genetic markers, as the technique of simple repeated sequences loci (SSR), which allows the analysis of the population structure and genetic diversity, making it possible to characterize the sampled populations. The objective of this study was to analyze the genetic variability of populations of T. angustula sampled using the technique SSR and verify the interaction of molecular markers used in other works with the morphological variants of T. angustula to check whether there is a marker that differentiates genetically. A total of 60 individuals (five per nest) were sampled in Maringá, Cianorte and Terra Boa, Paraná state, south of Brazil. Access to genetic variability was performed by analysis of four microsatellite loci. The results showed that all loci displayed polymorphism. The value of FST = 0.1173 obtained shows that populations are moderately differentiated and analysis of molecular variance indicates that 76% of the variation occurs within populations analyzed. The largest delta value K obtained by Bayesian inference estimated the actual number of people equal to 3 (K = 3). The analysis of interaction networks has shown that there are more interactions with isozymes, but that none of the analyzed molecular markers allowed separate T. angustula into two species.